Pengembangan Modul Ilustratif Berbasis Inkuiri Terbimbing Bermuatan Pendidikan Karakter - Hendri Noperi; Sarwanto Sarwanto; Nonoh Siti Aminah (SPEJ (Science and Physic Education Journal), 2021)
This study aimed to develop and determine the quality of the illustrative module of guided inquiry-based physics learning with character education. This research was a development research (R&D) which refers to the Borg & Gall model. The limited trial was carried out on 10 grade VII students and the expanded trial was carried out on 31 grade VIIA students at SMP Negeri 24 Surakarta. The data were taken using test techniques for cognitive learning outcomes, and observation techniques for character and psychomotor learning outcomes. Furthermore, it was analyzed by using two-sample paired t-test, while the psychomotor and affective learning outcomes were analyzed using the Friedman test. The results showed that the illustrative module of guided inquiry-based Physics learning containing character education was developed to have a total average score of 265.5 with the "very good" category. In conclusion, there was an increase in student learning outcomes after following the learning process using this developed illustrative module. Key words: Learning Outcomes, Product Quality, Illustration Modules, Research and Development